Lambert‐Eaton myasthenic syndrome with primary thymic marginal zone B‐cell lymphoma: A case report. Issue 5 (18th April 2023) - Soma, Toshihiko; Matsumoto, Akira; Shoji, Tsuyoshi; Katakura, Hiromichi
Abstract: Lambert‐Eaton myasthenic syndrome (LEMS) is an autoimmune paraneoplastic syndrome with proximal muscle weakness, that often complicates small cell lung cancer. It is known that neurological symptoms do not improve with malignancy treatment alone in many LEMS patients, therefore treatment is often difficult. Since Lambert‐Eaton myasthenic syndrome is a rare disease with a frequency of about 1/100 that of myasthenia gravis, there are only a few case reports on malignancy complications other than small cell lung cancer. We report a LEMS patient in his 40s who was found to have an anterior mediastinal mass. We performed surgical resection and confirmed the diagnosis of primary thymic marginal zone B‐cell lymphoma by pathological diagnosis using immunostaining. Thymectomy and malignant lymphoma treatment with rituximab had no effect on neurological symptoms. The neurological symptoms improved only after we provided comprehensive care with the haematology, neurology, and rehabilitation department. Abstract : Lambert‐Eaton myasthenic syndrome (LEMS) is a condition in which antibodies are produced against voltage‐gated calcium channels in presynaptic nerve endings, resulting in an inability to release acetylcholine. It is characterized by fatigue and weakness of the proximal muscles of the extremities and is complicated by ocular symptoms, autonomic symptoms, and cerebellar ataxia. We report the case of a patient in whom comprehensive care with multiple departments successfully improved LEMS symptoms with primary thymic marginal zone B‐cell lymphoma.